Evaluating the Effect of Building Envelope on Thermal Performance in Cold and Warm Climate Regions of Turkey (European Journal of Engineering Science and Technology, 2020)
Buildings consume significant amount of energy to keep interior environment at comfort conditions. Most heat losses occur in building envelope, causing the interior comfort conditions to be affected negatively. This leads buildings to consume more energy for keeping interior temperature at comfort level. This paper aims to propose building envelope details that limits the energy consumption and meets the required thermal comfort conditions for Erzurum city, locating at the coldest region in Turkey, and Mardin city, locating at the warmest region in Turkey. There is limited information about energy conservation of buildings in Erzurum city, and comparing of modern and traditional materials’ performances for both warm and cold regions in Turkey. Traditional buildings in Erzurum and Mardin cities have been constructed mostly as masonry which is traditional construction technic, whereas modern buildings are mostly built as reinforced concrete structural system. In this paper, the effect of building envelope on thermal performance has been analyzed for Erzurum and Mardin cities. 25 different building envelope detail alternatives, made up of modern and traditional materials with different insulation and covering materials, have been designed. Reinforced concrete, autoclaved aerated concrete and perforated brick have been chosen as a core material for modern building envelope details, whereas masonry stone, adobe brick and wooden frame have been chosen for traditional building envelope details. In the second part of study, different building envelope alternatives have been modelled in Design Builder software with Energy Plus simulation engine. Heating, cooling and total energy loads of these alternatives have been calculated for Erzurum and Mardin cities. The results of simulation are provided along with the evaluation and comparison. It was showed that adobe brick alternative has the lowest total energy consumption among all building envelope alternatives for both cities.